(untitled) (International Journal of Engineering and Computer Science, 2017)
Sumbawanga city, with population of about 90 thousand has experienced several damaging earthquakes from Kanda Fault System which is a seismically active fault in eastern side, encompassing Lake Rukwa and Lake Tanganyika basins. The magnitude 7.2 earthquake of July 1919 is one of the historical earthquakes from Kanda fault that generated damaging ground motions centered in Sumbawanga city while reaching several town/cities situated up to several kilometers from its epicenter. The historical earthquakes information of the region indicates that large earthquakes are expected in near future from the Kanda fault system. The Community Earthquake Early Warning System (CEEWS) are tools used to capture earthquakes onset time and ground motion levels in communities for emergency responses. To prepare for future emergency management of magnitude 7.2 earthquakes in Sumbawanga city, the study evaluates the warning times possible from the deployment of CEEWS in the city. Warning times calculated by simulating the event, indicates that Sumbawanga city will have approximately 8 second of warning times before the arrival of strong shaking if the processing and transmission delays are minimal. Warning times are meant to allow the appropriate emergency precautionary actions to be taken by the government officials, companies and individuals during the imminent earthquakes.